Cotyledonoid Dissecting Leiomyoma of the Uterus: An Unexpected Diagnosis After Delivery - Rocha, Ana Carolina (2018)
Cotyledonoid dissecting leiomyoma, also known as Sternberg tumor, is a rare benign uterine tumor with a gross and radiological appearance that may suggest the possibility of a malignancy. We report a case of a thirty-eight-year-old female patient who presented with menorrhagia and abdominal pain one month after delivery by cesarean section. An ultrasound scan showed a heterogeneous pelvic mass, near the isthmic region, with 25 x 24 x 23 mm without vascularization so the possibility of placenta accreta could not be excluded. During hysterectomy, we also removed a small grey mass in the right ovary. Microscopic examination revealed a proliferation of a sparsely cellular tissue with extensive hyalinization and coagulative necrosis, composed of spindle shaped muscle cells without cellular atypia or mitoses. The patient is without evidence of recurrence one year and six months post-surgery.